"It's like two worlds apart": an analysis of vulnerable patient handover practices at discharge from hospital. Issue 1 (30th October 2012) - Groene, Raluca Oana; Orrego, Carola; Suñol, Rosa; Barach, Paul; Groene, Oliver
Abstract : Background: Handover practices at hospital discharge are relatively under-researched, particularly as regards the specific risks and additional requirements for handovers involving vulnerable patients with limited language, cognitive and social resources. Objective: To explore handover practices at discharge and to focus on the patients' role in handovers and on the potential additional risks for vulnerable patients. Methods: We conducted qualitative interviews with patients, hospital professionals and primary care professionals in two hospitals and their associated primary care centres in Catalonia, Spain. Results: We identified handover practices at discharge that potentially put patients at risk. Patients did not feel empowered in the handover but were expected to transfer information between care providers. Professionals identified lack of medication reconciliation at discharge, loss of discharge information, and absence of plans for follow-up care in the community as quality and safety problems for discharge handovers. These occurred for all patients, but appeared to be more frequent and have a greater negative effect in patients with limited language comprehension and/or lack of family and social support systems. Conclusions: Discharge handovers are often haphazard. Healthcare professionals do not consider current handover practices safe, with patients expected to transfer information without being empowered to understand and act on it. This can lead to misinformation, omission or duplication of tests or interventions and, potentially, patient harm. Vulnerable patients may be at greater risk given their limited language, cognitive and social resources. Patient safety at discharge could benefit from strategies to enhance patient education and promote empowerment.